Pearlite Spheroidisation and Microstructure Refinement Through Heavy Warm Deformation of Hot Rolled 55VNb Microalloyed Steel - Montaña, Y.; Idoyaga, Z.; Gutiérrez, I.; Iza-Mendia, A. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2022)
The microstructure evolution of 55VNb microalloyed steel during warm deformation via single pass uniaxial compression was researched, and the effect of deformation conditions on dynamic spheroidisation of cementite lamellae and ferrite conditioning for a range of deformation temperatures (600 °C to 700 °C) and strain rates (1 to 10 s −1 ) analysed. Cementite lamellae appear to subdivide irrespective of deformation temperature with the ferrite phase penetrating the pattern formed by the cementite crystallites, in turn confirming that the dissolution of this phase during deformation is an important mechanism leading to the break-up of plates and subsequent globulisation. EBSD measurements allowed orientation gradients leading to the final subdivision of the cementite to be determined. Ferrite softening during heavy warm deformation is attributed to dynamic recovery and continuous dynamic recrystallisation, although the evolution of this phase depends, to a great extent, on the region subject to study, as confirmed by local EBSD studies. Misorientation profiles obtained in different regions of ferrite and pearlite enabled the different stages of the microstructural evolution to be monitored for each phase, this being developed via a variety of mechanisms under the same deformation conditions. Finally, the increase in low angle boundary density correlates with the Zenner–Hollomon parameter, and a linear relation between the density of low angle boundaries and steady-state stress estimated for pearlite and ferrite was found, indicating that new boundaries would have been formed dynamically during deformation. High angle boundary density also increases with deformation, although this is almost irrespective of the temperature and strain rate applied.